Macroeconomics - Blanchard, Olivier (Singapore, 2003)
The Core -- Introduction -- A Tour of the world -- A Tour of the book -- The Short run -- The Goods market -- Financial markets I -- Goods and financial markets; the IS-LM model -- Financial market II: the extended IS-LM model -- The Medium run -- The Labor market -- The Phillips curve, the natural rate of unemployment, and inflation -- From the short to the medium run: the IS-LM-PC model -- The Long run -- The Facts of growth -- Saving, capital accumulation, and output -- Technological progress and growth -- Technological progress: the short, the medium, and the long run -- Extensions -- Expectations -- Financial markets and expectations -- Expectations, consumption, and investment -- Expectations, output, and policy -- The Open economy -- Openness in goods and financial markets -- The Goods market in an open economy -- Output, the interest rate, and the exchange rate -- Exchange rate regimes -- Back to policy -- Should policy maker be restrained? -- Fiscal policy: a summing up -- Monetary policy: a summing up -- Epilogue: the story of macroeconomics
Keywords: Macroeconomics